Advances in mass spectrometry‐based glycomics—An update covering the period 2017–2021. Issue 1 (27th October 2021) - Donohoo, Kaitlyn B.; Wang, Junyao; Goli, Mona; Yu, Aiying; Peng, Wenjing; Hakim, Md Abdul; Mechref, Yehia
Abstract: The wide variety of chemical properties and biological functions found in proteins is attained via post‐translational modifications like glycosylation. Covalently bonded to proteins, glycans play a critical role in cell activity. Complex structures with microheterogeneity, the glycan structures that are associated with proteins are difficult to analyze comprehensively. Recent advances in sample preparation methods, separation techniques, and MS have facilitated the quantitation and structural elucidation of glycans. This review focuses on highlighting advances in MS‐based techniques for glycomic analysis that occurred over the last 5 years (2017–2021) as an update to the previous review on the subject. The topics of discussion will include progress in glycomic workflow such as glycan release, purification, derivatization, and separation as well as the topics of ionization, tandem MS, and separation techniques that can be coupled with MS. Additionally, bioinformatics tools used for the analysis of glycans will be described.